Softening of the flux-line structure in La 1.8 - Sr 0.2 - CuO 4 measured by a vibrating reed - Rodríguez, E.; Luzuriaga, Javier; D’ Ovidio, Claudio A.; Esparza, Daniel Antonio (Comisión Nacional de Energía Atómica; Argentina)
Fil: Rodríguez, E. Comisión Nacional de Energía Atómica; Argentina